PROFIL CONTENT SCALES MINNESOTA MULTIPHASIC PERSONALITY INVENTORY-2 (MMPI-2) ADAPTASI INDONESIA PADA MAHASISWA SEMESTER 5 TA 2012/2013 FAKULTAS KEDOKTERAN UNIVERSITAS SAM RATULANGI MANADO - Astuti, Dwi W. P.; Kairupan, Barnabas H. R.; Elim, Christofel (UNIVERSITAS SAM RATULANGI, 2013)
Abstract: Stress factors derived from academic and non-academic aspects can cause mental disorders in medical students. Mental disorders can lead to the impairment of student cognitive development and learning, as well as impact on the performance or functionality as a doctor later. This study aimed to determine the mental status profile of the fifth semester students of the Faculty of Medicine University of Sam Ratulangi, Manado, by using the content scales of MMPI-2 mental health tests. This was a descriptive study using a cross-sectional design. A hundred students who were randomly selected had to fill in the MMPI-2 questionnaires. A univariate analysis was conducted to analyze the data by using the SPSS version 20. The results showed that of the total respondents the majority (56%) were 20 years old; females were 53%; from outside of North Sulawesi were those from tribes (66%), and regions (56%). Â The siblings (2 brothers) represented 38% while the second born 37%. Most parents worked as civil servants: 46% fathers, 49% mothers. All content scales showed a high profile with the greatest percentages on scales SOD (32%) and WRK (30%). Based on the high score of content scales, the most prominent content component scales were SODâ‚ (84.4%) and TRTâ‚ (62.5%). Conclusion: The profile of mental disorders among the fifth semester students of the Faculty of Medicine, University of Sam Ratulangi Manado, was generally low. Keywords: Content Scales, students, MMPI-2.Â Â Abstrak: Faktor-faktor stres yang berasal dari aspek akademik maupun non-akademik dapat menimbulkan gangguan mental pada mahasiswa kedokteran, yang berakibat lanjut berupa gangguan perkembangan kognitif dan belajar yang berdampak pada prestasi sekaligus fungsionalitas mereka sebagai dokter nanti. Penelitian ini bertujuan untuk mengetahui profil status mental mahasiswa semester 5 FK Universitas Sam Ratuilangi Manado berdasarkan content scales pada tes kesehatan mental MMPI-2. Penelitian ini bersifat deskriptif dengan cross-sectional design. Kuesioner MMPI-2 dibagikan pada 100 sampel mahasiswa yang dipilih secara acak. Analisis univariat dilakukan menggunakan program SPSS 20. Hasil penelitian menunjukkan sebagian besar responden berusia 20 tahun (56%), jenis kelamin perempuan (53%), berasal dari suku dan daerah di luar Sulawesi Utara (66% dan 56%), 2 bersaudara dan anak ke-2 dalam keluarga (38% dan 37%), dengan pekerjaan orang tua terbanyak PNS (46% dan 49%). Semua content scales menunjukkan profil tinggi dengan presentase yang terbesar pada skala SOD (32%) dan WRK (30%). Berdasarkan skor tinggi content scales, content component scales yang paling menonjol ialah SODâ‚ (84,4%) dan TRTâ‚ (62,5%). Simpulan: Profil gangguan mental pada mahasiswa semester 5 Fakultas Kedokteran Universitas Sam Ratulangi Manado secara umum rendah. Kata kunci: content scales, mahasiswa, MMPI-2.